Identification of an endothelial cell cofactor for thrombin-catalyzed activation of protein C. - Esmon, C T (1981)
Perfusion of the myocardium with protein C in the presence of thrombin (EC 3.4.21.5) elicits a potent anticoagulant activity, which is identified as activated protein C on the basis of synthetic substrate hydrolysis and anticoagulant properties. The rate of activated protein C formation during the transit through the myocardium is at least 20,000 times that of thrombin-catalyzed activation of protein C in the perfusion solution. The capacity of the heart to activate protein C is maintained for at least 1 hr when thrombin is present in the perfusate, but decays (half-life approximately 30 min) once thrombin is omitted. Addition of diisopropyl-phospho-thrombin increases this decay rate more than 10-fold. Coperfusing diisopropylphospho-thrombin with active thrombin lowers the amount of protein C activation in the myocardium. Cultured monolayers of human endothelium enhance the rate of thrombin-catalyzed protein C activation. As with myocardium, the activation rate is inhibited by including diisopropylphospho-thrombin in the medium. It is proposed that the surface of vascular endothelium provides a cofactor that enhances the rate of protein C activation by thrombin.